Countermeasure Policy on Mining Crime under The Legal Progressive Perceptive - Faisal, Faisal; Rahayu, Derita Prapti (Faculty of Law, Universitas Sebelas Maret, 2021)
The complexity of mining business governance affects rational actions to tackle mining crime using the criminal policies in a progressive legal dimension. This research focuses on dealing with mining crime using criminal policies and rational efforts in the progressive legal dimension. It was conducted using normative legal research method using secondary data obtained from primary and secondary legal materials. The urgency of this research is to provide guidance towards the application of appropriate rules of mining for the actors in the business. It was also directed to provide references in mining law enforcement through an integral policy. The results showed that criminal policy through penal means in the formulation stage has the ability to regulate licensing crimes, corporate crimes, crimes against reclamation, and criminal obstruction of mining businesses. Moreover, the application stage involves the legal construction of material and formal offenses while the execution stage requires integral law enforcement. It is also important to note that the non-penal means which focuses on prevention maps potential actors with the ability to create the victims while the secondary prevention maps the mining areas with potential conflicts. This means the progressiveness of mining criminal policies rationally in the progressive law dimension enforces certainty and basic ideas underlying the norms.